Influence of sintering temperature on phase formation, microstructure and dielectric properties of calcium and strontium Doped BNT ceramics prepared via combustion technique - Sittiketkorn, Panadda; Laowanidwatana, Artid; Vittayakorn, Naratip; Bongkarn, Theerachai (My University, 2013)
Influence of sintering temperature on phase formation, microstructure and dielectric properties of calcium and strontium doped BNT ceramics (BNTST20 and BNTCT2) were investigated. The BNTST20 and BNTCT2 ceramics were prepared using the combustion technique. The structural phase of the BNTST20 ceramics indexed in a cubic phase, while the BNTCT2 ceramics indexed in a rhombohedral phase. The average grain size tended to increase with increasing sintering temperature. The density and the dielectric constant at Curie temperatures increased with increasing sintering temperature up to 1200°C and 1150°C, thereafter they decreased for BNTST20 and BNTCT2 ceramics, respectively. Moreover, the highest density (5.59 and 5.57 g/cm3) ceramics exhibited the highest dielectric constant at Curie temperatures (∼4733 and ∼3218) for BNTST20 and BNTCT2, respectively. The ferroelectric properties were also investigated. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Bismuth sodium titanate; dielectric constant; hysteresis loop; phase formation